2019
DOI: 10.1002/jcla.23042
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of 5‐HTR6 gene polymorphism with vestibular migraine

Abstract: Objective To investigate the correlation of 5‐hydroxy tryptamine receptor 6 (5‐HTR6) gene polymorphism with vestibular migraine (VM). Methods A total of 92 VM patients were enrolled as the observation group, and 100 healthy people receiving physical examinations as the control group. Their general clinical information was collected, and the level of 5‐HT in plasma and the vestibular function test indexes were detected. Moreover, the polymorphism of 5‐HTR6 rs770963777 was detected with the TaqMan‐MGB probe. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The genetic association studies retrieved have reported allelic variants in the HTR6 and PRG genes associated with VM (Lee et al, 2007 ; Wu et al, 2020 ). Replication studies are needed to validate these results.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic association studies retrieved have reported allelic variants in the HTR6 and PRG genes associated with VM (Lee et al, 2007 ; Wu et al, 2020 ). Replication studies are needed to validate these results.…”
Section: Discussionmentioning
confidence: 99%
“…Another pathophysiological mechanism in VM may be a visuo-vestibular problem, as patients with VM have a longer duration of post-rotatory nystagmus compared to healthy controls or ordinary migraine patients [39]. Plus, a genetic component in the pathogenesis of VM has been identified [28,40].…”
Section: Pathophysiology Of Vmmentioning
confidence: 99%